Preparation method of microfilament composite material with programmable microwave response
By processing microwires under different annealing current conditions and adjusting their arrangement and structure in the matrix, the problems of structural complexity and equipment bulkiness in existing microfilament supercomposites when modulating electromagnetic responses are solved, and electromagnetic performance programmability and microwave tunability in a wide frequency range are achieved.
Patent Information
- Application Number
- CN202411873914.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-28
AI Technical Summary
Existing microfilament supercomposites have problems of structural complexity and equipment bulkiness when modulating electromagnetic responses, making it difficult to achieve wider microwave tunability.
Microwave performance of microfilament composites is programmed by processing single microwires under different annealing current conditions and adjusting their arrangement, line concentration and period in the matrix to achieve different line-to-line interactions, thereby adjusting their transmission parameters.
The programmability of the final electromagnetic performance over a wide frequency range is achieved, the structure is simplified, the device is reduced, and the microwave tunability is improved.
Smart Images

Figure CN119710330A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano composite materials, in particular to a method for preparing a microwire composite material with programmable microwave response. Background Art
[0002] Microwire supercomposite is a new type of composite material that combines the concepts of microwire and metamaterial. Microwire supercomposite is a composite material with metamaterial characteristics obtained by incorporating ferromagnetic microwires into a polymer matrix to achieve specific electromagnetic properties. It has attracted widespread attention due to its giant magnetoresistance effect (GMI effect) and tunable soft magnetic properties, which make it have potential applications in electronic sensing, electromagnetic shielding, microwave absorption and structural health monitoring.
[0003] Ferromagnetic microwires as building blocks endow composites with advantages such as low filler content requirements, high field / stress sensitivity, dual negative metamaterial properties, and excellent mechanical properties. The above functions are achieved through traditional strategies such as adjusting topological factors (such as microwire length and periodicity) and applying external stimuli (such as magnetic fields or stress). However, methods based on microwire geometry modulation may complicate the topological arrangement of microwires or require considerable microwire loads to achieve good adjustability. The implementation of external stimuli is also problematic because in the case of applied magnetic fields, bulky magnets are required to expand the operating frequency band, and in the case of applied stress, strong interfacial bonding is required to ensure uniform stress distribution. The way to adjust the electromagnetic response has certain limitations.
[0004] Although the above-mentioned microwire supercomposites achieve electromagnetic functions, the limitations of modulating their electromagnetic responses are a hindrance to device miniaturization. Therefore, it is necessary to simplify the structure while achieving broader microwave tunability. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a programmable microwave-responsive microwire composite material, by programming the microwave performance of the microwire composite material under different annealing current conditions and different arrangements, wire concentrations and periods in the matrix of a single microwire, and arranging the structure to achieve different interactions between wires, thereby adjusting its transmission parameters, providing a feasible platform for programming and specifying the final electromagnetic performance of the microwire array composite material over a wide frequency range.
[0006] To achieve the above object, the present invention provides a method for preparing a microwire composite material with programmable microwave response, comprising the following steps:
[0007] S1, adding the master alloy into the glass tube, and then placing it in a high-frequency induction heater for heating treatment to obtain a molten master alloy, and the glass tube portion close to the molten master alloy becomes soft;
[0008] S2, simultaneously stretching and rapidly cooling the molten master alloy, and winding it into a coil to obtain a cast micron wire (marked as A);
[0009] S3, performing annealing treatment on the cast micro-wires at a direct current range of 20 mA to 40 mA to obtain annealed micro-wires (marked as X);
[0010] S4. Embed one or both of the cast microwires or annealed microwires into a silicone resin matrix in a certain arrangement and combination to obtain a microwire composite material.
[0011] Preferably, in S1, the master alloy is Co 60 Fe 15 Si 10 B 15 .
[0012] Preferably, in S3, the annealed microwires include 20 mA annealed microwires, 30 mA annealed microwires (marked as B) and 40 mA annealed microwires (marked as C).
[0013] Preferably, S4 is specifically:
[0014] A plurality of same type of cast microwires or annealed microwire arrays are integrated into a silicone matrix to obtain a microwire composite material.
[0015] Preferably, S4 is specifically:
[0016] A plurality of cast microwires and annealed microwires are arrayed into a silicone matrix, the number of cast microwires or annealed microwires is increased successively by 2n, n=1, 2, 3, and n annealed microwires are inserted between the cast microwires to obtain a microwire composite material.
[0017] Preferably, in S4, the fixed wire spacing of the microwire composite material is 1 to 2 mm.
[0018] Therefore, the present invention adopts the above-mentioned method for preparing a microwire composite material with programmable microwave response, and the beneficial effects are as follows:
[0019] (1) The present invention programs the microwave performance (microwave response) of microwire composites by using a single microwire under different annealing current conditions and different arrangements, wire concentrations and periods in the matrix. The microwire is regarded as a unique code corresponding to its microstructure. The code type is defined by the annealing current intensity. The code pattern is determined by the microwire combination mode, which can largely determine the transmission absorption frequency and amplitude of the composite material. By changing the maximum "effective" area formed by the sequential combination of cast microwires and annealed microwires, the conductivity of the entire array can be adjusted, thereby affecting the transmission absorption frequency of the composite material.
[0020] (2) The present invention utilizes annealing to reduce its internal damping, thereby achieving a red shift in frequency after the annealed microwires are added to the array; in addition, through a single component control method, it can also be used to predict the transmission and absorption bands of different microwire arrays, providing a simpler and lower-cost platform than the stimulation / hybridization-based method, and can be used to design microwave materials for intelligent wide-band applications.
[0021] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 1 is a characteristic diagram of an embodiment of a method for preparing a programmable microwave-responsive microwire composite material of the present invention under different annealing conditions, wherein (a) is an XRD spectrum of the cast microwire and the annealed microwire - structural characteristics, (b) is a DSC curve of the cast microwire and the annealed microwire - thermal characteristics, (c) is an MH loop of the cast microwire and the annealed microwire - magnetic characteristics, and (d) is a conductivity change diagram of the cast microwire and the annealed microwire - electrical characteristics;
[0023] Figure 2 Schematic diagram of the arrangement of Example 2 of a method for preparing a programmable microwave-responsive microwire composite material of the present invention, wherein (a) is of the same type, (b) is a cast microwire and an annealed microwire B, and (c) is a cast microwire and an annealed microwire C;
[0024] Figure 3 It is a dynamic interaction schematic diagram of Example 2 of a method for preparing a programmable microwave-responsive microwire composite material of the present invention;
[0025] Figure 4 1 is a transmission spectrum diagram of an embodiment of a method for preparing a programmable microwave-responsive microwire composite material of the present invention, wherein (a) is a single cast microwire and an annealed microwire of the same type, and (b) and (c) are microwire composite materials of Example 2;
[0026] Figure 5 1 is a schematic diagram of the arrangement of Example 3 of a method for preparing a programmable microwave-responsive microwire composite material of the present invention, wherein (a) is a cast microwire, (b) is an annealed microwire B, (c) is an annealed microwire C, (d) is a cast microwire and an annealed microwire in a repeated manner, and (e) is a cast microwire and an annealed microwire in an alternating manner;
[0027] Figure 6It is a transmission spectrum diagram of an embodiment of a method for preparing a programmable microwave-responsive microwire composite material of the present invention, wherein (a) is 2 mm of the same type A, (b) is 2 mm of the same type B, (c) is 2 mm of the same type C, (d) is 1 mm of the same type A, (e) is 1 mm of the same type B, and (f) is 1 mm of the same type C;
[0028] Figure 7 1 is a frequency dependence relationship diagram of the transmission coefficient-S21 of an embodiment of a method for preparing a microwire composite material with programmable microwave response of the present invention, wherein (a) is AX, (b) is AAXX, (c) is AAAXXX, (d) is AXAX, and (e) is AXAXAX;
[0029] Figure 8 It is a schematic diagram of electromagnetic waves of an embodiment of a method for preparing a programmable microwave-responsive microwire composite material of the present invention, wherein (a) is AAAXXX, (b) is AXAXAX, and (c) is the near-field interaction of an AXAXAX array with a wire spacing of 1 mm;
[0030] Fig. 9 It is a programming strategy diagram of an embodiment of a method for preparing a programmable microwave-responsive microwire composite material of the present invention, wherein (a) is 2 mm and (b) is 1 mm. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0032] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0033] Embodiment 1
[0034] A method for preparing a microwire composite material with programmable microwave response, specifically comprising:
[0035] First, the selected component is Co 60 Fe 15 Si 10 B 15 5g of master alloy (the specific composition ratio is adjusted within a certain range) is placed in a Pyrex glass tube and placed in a high-frequency induction heater. The heating time is between 2min and 20min, and the heating temperature is adjusted according to the melting point of the master alloy to ensure that the master alloy can be completely melted. When the master alloy melts, the part of the glass tube close to the molten master alloy becomes soft and surrounds the metal droplet.
[0036] Secondly, the molten master alloy is stretched and rapidly cooled at the same time, a glass capillary is pulled out from the softened glass part, and it is wound on a rotating coil. By adjusting the stretching conditions (such as stretching speed and stretching length), the molten master alloy is filled into the glass capillary, forming a cast micron wire with a metal core completely covered by a glass shell. Its total diameter is 35.4μm and the metal core diameter is 27.2μm.
[0037] Thirdly, in order to change the structural characteristics of the cast microwires and thus adjust their electromagnetic properties, the cast microwires (marked as A) were annealed at different DC currents (20 mA to 40 mA) for 5 to 15 minutes to obtain annealed microwires. Before annealing, the glass shells at both ends of the cast microwires were mechanically removed to ensure adequate electrical contact.
[0038] In addition, during the annealing process, a digital multimeter was used to monitor the DC resistance after each current application. The resistance of the microwires annealed at a higher current value (such as close to or reaching 40mA) dropped significantly. This may be related to the change in the internal structure of the microwires during the current annealing process.
[0039] Finally, the cast microwires and annealed microwires were embedded into a silicone matrix in different arrangements and combinations to obtain microwire composites.
[0040] Embodiment 2
[0041] The difference from the first embodiment is that the same type of microwires are used, namely, the cast microwire A (0 mA), the annealed microwire B (30 mA) or the annealed microwire C (40 mA). Figure 2 As shown in (a) in .
[0042] Combine the cast microwire A and the annealed microwire B, such as Figure 2 As shown in (b) in FIG. Or the cast microwire A is combined with the annealed microwire C, as shown in FIG. Figure 2 As shown in (c), the size of the microwire composite material is 22.86×10.16×2mm 3 , the wire spacing is fixed at 2 mm, and the dynamic microwire interactions of different microwire arrangements are shown in Figure 3 shown.
[0043] Embodiment 3
[0044] The difference from the first embodiment is that the number of microwires 2n (n=1, 2, 3) of the same type is increased in sequence and the array contains different arrangements of cast microwires A or annealed microwires B (30 mA) or annealed microwires C (40 mA). The size of the microwire composite material is 22.86×10.16×2 mm 3, the fixed wire spacing ranges from 1mm to 2mm. Figure 5 shown.
[0045] Experimental Testing
[0046] The effects of annealing on the structure and thermal characteristics of microwires are analyzed as follows:
[0047] like Figure 1 As shown in (a) in Figure 1, the wire still maintains its amorphous structure even under the annealing condition with a maximum current intensity of 40 mA. Therefore, the annealing of the wire mainly causes stress relief, structural relaxation and homogenization.
[0048] like Figure 1 As shown in (b), the DSC curves of the as-cast microwire (0 mA), 30 mA annealed microwire, and 40 mA annealed microwire show the effect of annealing on structural relaxation and crystallization process. For the as-cast microwire, there is a very small Curie peak (TC) near 635K, reflecting the large internal stress of the two-step crystallization process (TX). Annealing at 30 mA and 40 mA causes TC to split into two peaks. This confirms the existence of two magnetic phases and the appearance of small clusters under different local environments. The increase and broadening of TX after annealing relative to the as-cast microwire indicates that the proportion of nanocrystals in the annealed microwire sample is larger (the area under the peak is proportional to the proportion of nanocrystals), and the stress is also relieved.
[0049] like Figure 1 As shown in (c), the MH loops of the as-cast microwires and the annealed microwires are shown. The coercivity drops sharply from 15Oe for the as-cast microwires to 0.8Oe for the 40mA annealed microwires, proving that the magnetic softness of the annealed microwires is improved. In addition to stress relief, a significant internal stress redistribution is also produced. For the as-cast microwires, the larger internal stress leads to a larger magnetoelastic anisotropy during the casting process. The annealed microwires gradually produce anisotropic local magnetization (the slope of the loop gradually decreases). Compared with the 30mA annealed microwires, the slightly larger anisotropy of the 40mA annealed microwires may be due to the compactness of the crystallization. In addition, the increase in surface defects and roughness may also be the reason for the drastic changes in magnetic properties.
[0050] After each application of current, the DC resistance of the microwires in the 40 mA annealed state shows a considerable decrease, indicating that crystallization may have begun. This decrease in resistance is related to the increase in temperature caused by the current, which leads to an increase in grain size, which will result in a decrease in electron scattering at the grain boundaries. Crystallization starts from the surface of the alloy wire and grows slowly. Crystal-cobalt islands are uniformly nucleated on the alloy wire, resulting in structural relaxation of the alloy wire when annealed at 40 mA, and an increase in conductivity, such as Figure 1 (d) in.
[0051] In summary, the structural relaxation and stress relief under annealing are manifested as changes in the intensity and position of the Curie peak, the formation of fine nanocrystals, the reduction of anisotropy field and coercivity, and the improvement of conductivity. These structural changes after annealing will have a key impact on the electromagnetic properties of microwire composites.
[0052] The microwave characterization of the effects on microwire organization and alignment is as follows:
[0053] A single cast microwire (0 mA cast microwire), annealed microwire (20 mA annealed microwire, 30 mA annealed microwire and 40 mA annealed microwire) of the same type and the microwire composite material prepared in Example 2 were used for microwave response.
[0054] like Figure 4 As shown in (b) and (c) of Figure 1, for composites containing a combination of as-cast and annealed microwires, the arrangement of the microwires has a profound effect on the transmission amplitude and transmission dip frequency of the composite. When as-cast and annealed microwires, i.e., AAABBB and AAACCC, are added to the array in equal amounts, the transmission dip or dipole resonance gradually shifts to lower frequencies as the 30mA annealed microwires are replaced by the 40mA annealed microwires. This trend is consistent with the results for composites containing the same type of wires (i.e., AAAAAA, BBBBBB, and CCCCCC), such as Figure 4 As shown in (a) in the figure, the red shift of the AAACCC sample is the most obvious. When the microwires are alternately arranged into ABABAB and ACACAC arrays, the transmission attenuation changes with frequency in the same trend, that is, it red-shifts with the addition of the 40mA annealed microwires. Finally, when the microwires in the middle of the array (ABABAB and ACACAC) are exchanged, that is, ABBAAB and ACCAAC, the critical frequency shifts again on the side of the 40mA annealed microwires. The transmission amplitude of the microwire composite also decreases with the addition of annealed microwire C to the array.
[0055] Considering the differences in domain structure and magnetic tensor between the as-cast and annealed microwires, the changes in the transmission spectral features of the composites can be explained by dynamic microwire interactions. In this case, since the 2 mm microwire spacing is still too wide to generate meaningful magnetoelastic energy, the dynamic microwire interaction is caused by coupling with the electric component of the incident wave rather than magnetostatic coupling. In the case of AAAXXX (where X corresponds to 30 mA or 40 mA annealed wires), as Figure 3As shown, the maximum "effective" area consisting of structurally identical microwires (three A plus three X) with different conductivities is considered. When microwires of the same type are connected in parallel, the total cross-sectional area of the microwires increases, the effective resistivity decreases, and the skin effect is stronger. When the order of the microwire arrangement is changed, this "effective" area decreases, that is, three microwires of the same type (AAAXXX) are reduced to two (AXXAAX) and one (AXAXAX), which affects the equivalent conductivity and thus changes the transmission dip frequency of the composite material. In addition to structural relaxation, annealing of the microwires also reduces the relaxation rate or internal damping Γ of the nanostructure. Annealing of the microwires leads to an increase in relaxation time, which may be related to the transmission dip of the array containing annealed microwires gradually switching to lower frequencies.
[0056] The effects of microwave on microwire concentration and period are as follows:
[0057] like Figure 6 As shown in Figure 1, when the number of wires increases by 2n (n = 1, 2, 3) and the wire spacing decreases from 2 mm to 1 mm, all composite materials show obvious band-stop characteristics. For both spacings, increasing the number of microwires in the array leads to a blue shift in the transmission dip frequency and a decrease in the transmission amplitude. By using Eq. (1), we get fres = 10.44 GHz, which is consistent with Figure 6 The identification dip angle of the four-wire array with 2 mm spacing in (a) is close. Near this antenna resonance, any change in the impedance of the microwires will result in a change in the transmission spectrum and the Lorentz resonance. Replacing the cast wires with annealed microwires slightly decreases the transmission amplitude and gradually redshifts the transmission dip frequency, regardless of the number and spacing of the microwires ( Figure 6 (b, c, e, and f) in Figure 5). This red shift is associated with the gradual elimination of internal stresses and the induced structural relaxation during annealing and the reduction of internal damping, Γ. Finally, reducing the microwire spacing in the array has a significant effect on the transport properties of composites containing the same microwire type ( Figure 6 (df)), which is caused by the dynamic microwire-microwire interaction. In this case, the dynamic microwire interaction also mainly comes from the coupling of the electric and magnetic components of the incident wave, rather than static magnetoelastic coupling, because the microwire spacing of 1mm or 2mm is still too wide to produce meaningful magnetoelastic properties. Reducing the microwire spacing from 2mm to 1mm causes the transmission dip frequency of the composite to red-shift. In addition, the change of the dip frequency as a function of the number of microwires is less obvious in the case of 1mm spacing than in the case of 2mm spacing. In this case, the microwire medium becomes more dense, resulting in a stronger coupling of the dynamic magnetization of the microwires with the electromagnetic field, and therefore, the electromagnetic energy coupled to the microwire array can effectively propagate from microwire to microwire within the component.
[0058] Figure 7The transmission coefficient - S21 of the composite composed of cast microwires and annealed microwires with a spacing of 2 mm and 1 mm between them is shown. Similar to the case of composites containing the same type of microwires ( Figure 6 ), increase AX( Figure 7 (a)) and the AAXX array ( Figure 7 The number of microwires in (b, c), where X represents 30 mA or 40 mA annealed microwires, results in a blue shift in the transmission dip frequency regardless of the microwire spacing. Adding progressively annealed microwires to the structure, i.e. replacing B with C, results in a red shift in the transmission dip frequency, similar to the case of the same type of line array ( Figure 6 ). When the microwire pitch is reduced to 1 mm, the transmission dip undergoes a clear red shift relative to the array containing 2 mm pitch microwires, thus following the same trend found in composites containing the same type of microwires.
[0059] For composite materials containing microwire arrays with different microstructures, when waves hit such inhomogeneous composite systems, amplitude reduction and wave phase shift occur, resulting in different wave propagation attenuation modes, e.g. Figure 8 As shown. Under the action of electromagnetic waves, electric dipoles and magnetic dipoles are formed in the metal wire, and their dipole fields are closely related to the distribution of magnetic moments, and thus to the microstructure of the metal wire. Due to different structural relaxations and magnetic properties (i.e., magnetic permeability, coercivity, magnetic domains, etc.), each microwire responds differently to the incident wave and precesses with its own damping under the torque generated by the microwave magnetic (electric) field. Due to the electrical and magnetic responses of the microwires, the overlap and closure of the magnetic field leads to stronger constraints on wave and slow wave propagation. In addition, at larger periodicities, replacing the annealed wire (B) with (C) has a negligible effect on the resonant frequency shift ( Figure 8 (a) and (b)). This is mainly due to the fact that both samples retain their nanocrystalline properties after annealing, with no obvious structural changes and weak inter-wire coupling strength. When the microwire period is reduced to 1 mm, i.e., when near-field interactions dominate, an additional configuration is expected to emerge, namely, flow closure between fields from the same type of microwires in the array, and their overlap with neighboring microwires ( Figure 8 (c)).
[0060] like Fig. 9 As shown in Figure 2, the overall design criteria for programming strategies based on the effects of wire microstructure, wire number, and wire period on the transmission dip frequency are summarized. A and f X Between (where f A is the frequency of the composite material containing only cast wire, f Xis the frequency of the composite containing only annealed wire). This range can be widened or shortened depending on the degree of annealing of the wire. Increasing the concentration of wire will cause a blue shift in the resonant frequency. The larger the wire periodicity, the more obvious the blue shift will be due to the increase in conductivity ( Fig. 9 (a)). Reducing the periodicity of the microwires red-shifts the resonant frequency due to stronger near-field interactions and efficient wave propagation within the array ( Fig. 9 (b)). Finally, for as-cast and annealed wires with different arrangements, alternating microwires in an array allows for higher transmission dip frequencies due to the effects of flow closure and overlap on the wave propagation decay modes. Controlling the individual properties of each resonant wire in the array collectively facilitates the tuning of macroscopic properties such as electromagnetic response. This programming strategy paves the way to explore and realize new functionalities by designing composites based on the concepts of ordered structures and the influence of the functional units themselves.
[0061] Therefore, the present invention adopts the above-mentioned method for preparing a programmable microwave-responsive microwire composite material, and programs the microwave performance of the microwire composite material by using a single microwire under different annealing current conditions and different arrangements, wire concentrations and periods in the matrix. The arrangement structure realizes different interactions between wires, thereby adjusting its transmission parameters, providing a feasible platform for programming and specifying the final electromagnetic performance of microwire array composites over a wide frequency range.
[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a microwire composite material with programmable microwave response, characterized in that: The following steps are involved: S1, adding the master alloy into the glass tube, and then placing it in a high-frequency induction heater for heating treatment to obtain a molten master alloy, and the glass tube portion close to the molten master alloy becomes soft; S2, simultaneously stretching and rapidly cooling the molten master alloy, and winding it into a coil to obtain a cast micron wire; S3, annealing the cast microwires at a direct current range of 20 mA to 40 mA to obtain annealed microwires; S4. Embed one or both of the cast microwires or annealed microwires into a silicone resin matrix in a certain arrangement and combination to obtain a microwire composite material.
2. The method for preparing a programmable microwave-responsive microwire composite material according to claim 1, characterized in that: In S1, the master alloy is Co 60 Fe 15 Si 10 B 15 .
3. The method for preparing a programmable microwave-responsive microwire composite material according to claim 1, characterized in that: In S3, the annealed microwires include 20 mA annealed microwires, 30 mA annealed microwires and 40 mA annealed microwires.
4. The method for preparing a programmable microwave-responsive microwire composite material according to claim 1, characterized in that: S4 is specifically: A plurality of same type of cast microwires or annealed microwire arrays are integrated into a silicone matrix to obtain a microwire composite material.
5. The method for preparing a programmable microwave-responsive microwire composite material according to claim 1, characterized in that: S4 is specifically: A plurality of cast microwires and annealed microwires are arrayed into a silicone matrix, the number of cast microwires or annealed microwires is increased successively by 2n, n=1, 2, 3, and n annealed microwires are inserted between the cast microwires to obtain a microwire composite material.
6. The method for preparing a programmable microwave-responsive microwire composite material according to claim 1, characterized in that: In S4, the fixed wire spacing of the microwire composite material is 1 to 2 mm.